Effectiveness of Sparcs on The Reading Comprehension Performance of Grade 6 Learners - Suplaag, Melbert Cagang; Sheena Atasha Rama PANTUJAN; Pauleen Kate Gimarino ROJAS; Julie Rose LAHOY; Anamie Dela Peña BAYER (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This study evaluated the effectiveness of the Sustainable Program for Accelerating Reading Comprehension Skills (SPARCS) in improving the reading comprehension performance of grade 6 learners at Poblacion, Liloan, Cebu. Using a true experimental research design, the study involved a control group and an experimental group, with pre-test and post-test assessments based on the PHIL-IRI reading comprehension tests. Findings indicate that before the intervention, both groups had similar reading comprehension levels, with most learners classified under the "frustration" level. After the implementation of SPARCS, the experimental group showed a significant improvement, with a majority reaching the "independent" level, while the control group exhibited minimal progress. Additionally, participants rated the program’s acceptability as "Highly Acceptable" in terms of reading activities, materials, and tutor support while learning outcome was rated “Acceptable.” One indicator under learning outcome— handling more challenging texts—was rated “Less Acceptable,” highlighting an area for improvement. Based on these findings, enhancements to SPARCS are recommended, including increased tutor support, and the inclusion of more complex reading selections. The study concludes that SPARCS is an effective intervention for improving reading comprehension of the grade 6 learners and provides a foundation for further research and program development.